2019
DOI: 10.1136/injuryprev-2018-043061
|View full text |Cite
|
Sign up to set email alerts
|

Using street imagery and crowdsourcing internet marketplaces to measure motorcycle helmet use in Bangkok, Thailand

Abstract: IntroductionThe majority of Thailand’s road traffic deaths occur on motorised two-wheeled or three-wheeled vehicles. Accurately measuring helmet use is important for the evaluation of new legislation and enforcement. Current methods for estimating helmet use involve roadside observation or surveillance of police and hospital records, both of which are time-consuming and costly. Our objective was to develop a novel method of estimating motorcycle helmet use.MethodsUsing Google Maps, 3000 intersections in Bangko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Merali and colleague's street imagery study using google maps has been previously referred to in the introduction and further analysis of the data was done according to motorcyclist category and whether the streets were residential or not (Merali et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Merali and colleague's street imagery study using google maps has been previously referred to in the introduction and further analysis of the data was done according to motorcyclist category and whether the streets were residential or not (Merali et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This could include improved education or awareness as a result of ideas such as that which is presented in this manuscript, or improving law enforcement, increasing fines for non-compliance or making helmets more affordable and less cost to purchase. Merali and colleagues mention that street imagery in the future maybe automated via machine learning (Merali et al, 2020). That hence may facilitate the ease of capturing and/ or re-capturing data, analysis and re-analysis to monitor helmet usage rates in the future while also assessing and monitoring change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, researchers used street imagery available online and machine learning to estimate helmet use prevalence. 63 In another study, a large government dataset of road injuries and data mining techniques were used to predict road injury severity. 64…”
Section: Diagnosismentioning
confidence: 99%
“…In addition to phone and photo data, GSV images are another data source that are even more consistent, cost-effective, and scalable. Recent studies [320,[328][329][330] that have employed GSV images have shown the data's great potential for large-scale comparative analysis. For example, Goel et al [328] collected 2000 GSV images from 34 cities to predict travel patterns at the city level.…”
mentioning
confidence: 99%